Isoflurane rescue therapy for bronchospasm reduces intracranial pressure in a patient with traumatic brain injury. (2nd July 2016) - Gradisek, Primoz; Dolenc, Simon
Abstract: Primary objective : To assess the unusual use of a volatile anaesthetic for treatment of life-threatening bronchospasm in a patient with traumatic brain injury (TBI). Research design : Case report. Methods and procedures : This study presents a previously healthy 30-year-old man with severe TBI and bronchospasm-induced acute hypercapnia. He was treated with inhaled isoflurane in combination with monitoring of intracranial pressure (ICP) and regional cerebral blood flow (rCBF). Results : Three-day-long isoflurane treatment resolved drug-refractory bronchospasm, decreased airway pressure and improved gas exchange, even at a low end-tidal concentration (0.3–0.5 vol%). Although rCBF was increased by 18 ml min –1 100 g –1 during isoflurane treatment, there was a significant decrease in ICP (21 (SD = 3) mmHg, 9 (SD = 5) mmHg, 2 (SD = 3) mmHg; during pre-treatment, treatment and post-treatment, respectively; p < 0.001). Improved autoregulation due to lower partial pressure of carbon dioxide, restoration of carbon dioxide reactivity, isoflurane-induced regional differences in rCBF and improved microcirculation may have been responsible for the prompt and long-lasting normalization of ICP. The patient had no TBI-related disability at 6 months post-injury. Conclusions : Isoflurane at a low dose can be an effective and safe treatment option for drug-refractory bronchospasm in a patient with traumatic intracranial hypertension, provided that multimodality neuromonitoring is used.